Dichlorido{N,N-dimethyl-N '- 1-(pyridin-2-yl)ethylidene ethane-1,2-diamine-kappa N-3,N ',N ''}cadmium - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2011)
In the title compound, [CdCl2(C11H17N3)], the Schiff base acts as an N,N',N ''-tridentate ligand towards the Cd-II ion. Two Cl atoms complete a distorted square-pyramidal geometry around the metal atom. In the crystal, a C-H center dot center dot center dot Cl interaction connects pairs of molecules into centrosymetric dimers.